Family Life and HIV/AIDS Education (FLHE) as Predictor of Knowledge and Attitude to HIV/AIDS among Adolescents with Hearing Impairment in South-West, Nigeria (2012)
The menace of HIV/AIDS is a serious concern globally, especially the rate at which the disease spreads among adolescents with hearing impairment. This has been attributed to poor knowledge of and attitude to the incidence of HIV/AIDS, lack of personal skills coupled with inability of adolescents with hearing impairment to hear, comprehend and translate information about HIV/AIDS to functional use that could have helped them to cope with life challenges. Several studies have been carried out on the influence of Sexuality Education on adolescents without hearing impairment. However, there is a paucity of studies on the influence of Sexuality Education on adolescents with hearing impairment‟s knowledge of and attitude to HIV/AIDS. This study, therefore, investigated Family Life and HIV/AIDS Education as predictors of knowledge of and attitude to HIV/AIDS among adolescents with hearing impairment in South-West, Nigeria. The study adopted survey research design of ex-post facto type. Multi-stage sampling technique involving stratified random sampling, purposive and simple random sampling were employed to select states, schools and the participants in South-West, Nigeria. A total of 450 adolescents with hearing impairment were selected. Data were collected through research scale tagged Family Life and HIV/AIDS Education inventory consisting of Self-esteem Inventory (0.80), Goal Setting Inventory (0.62), Decision-making Inventory (0.60), HIV/AIDS‟ Knowledge Inventory (0.62) and HIV/AIDS Attitudinal Inventory (0.60). Six research questions were answered at the 0.05 level of significance. Data were analysed using descriptive statistics, Pearson Product Moment Correlation and Multiple regression. The independent variables namely, Self-esteem, Goal-setting and Decision-making showed significant relationship with the knowledge of adolescents with hearing impairment about HIV/AIDS in the following order: decision-making (r=0.551; p<.05), self-esteem (r=0.510; p<.05) and goal-setting (r=0.487; p<.05). The joint effect of the independent variables yielded a coefficient (R=0.616, p<.05). Decision-making mostly contributed to knowledge of HIV/AIDS among adolescents with hearing impairment (β=0.289, t=5.548; p<0.05) while goal-setting was the least (β=0.188, t=3.898; p<0.05). The independent variable, Self-esteem, Goal-setting and Decision-making also showed significant relationship with attitude of adolescent with hearing impairment to HIV/AIDS in the following order: decision-making (r=0.568; p<0.05), self-esteem (r=0.492; p<0.05) and goal-setting (r=0.488; p<0.05). There was a joint effect of the independent variables on the attitude of adolescents with hearing impairment to HIV/AIDS (R=0.618; p<0.05). Decision-making also contributed mostly to attitudes of adolescents with hearing impairment to HIV/AIDS (β=0.334, t=6.438, p<0.05) while goal-setting was the least (β=0.181, t=3.762; p<0.05). Family Life and HIV/AIDS Education skills in Self-esteem, Goal-setting and Decision-making showed significant influence on knowledge of and attitude to HIV/AIDS among adolescents with hearing impairment. Therefore, Federal government as well as other stakeholders concerned with education of adolescents with hearing impairment should be more pragmatic on the implementation and monitoring of Family Life and HIV/AIDS Education programme. This will help to reduce the spread of HIV/AIDS among adolescents with Hearing Impairment in Nigeria and enable them to achieve overall adjustment in life.